Seroprevalence of SARS-CoV-2 in Children Admitted to a Pediatric Ward of an Urban Hospital - Rama Kaja; Surendranath Mallavalli (Pediatric Infectious Disease)
A seroprevalence of SARS-CoV-2 study among pediatric patients in a South Indian urban hospital found 37% of children to be COVID-19 IgG positive in a 7-month period. Data reveals widespread asymptomatic infection among children. We may achieve herd immunity faster than other countries which might also increase vaccine effectiveness. Manifestations like suppurative cervical lymphadenitis and intussusception were seen with greater frequency in our study sample. Aim: To study the seroprevalence of SARS-CoV-2 among pediatric patients admitted in an urban hospital in South India. Methods: An analytical study was conducted using medical records of children admitted for various conditions in the pediatric ward of our non-COVID-19 hospital from July 2020 through January 2021, a total of 7 months. All patients were tested for SARS-CoV-2 antibodies using the Cellex q Cassette rapid test. Those with a positive RT-PCR or positive IgM were referred to designated hospitals. Result: We found 37% of the children to be COVID-19 IgG positive. Manifestations like suppurative cervical lymphadenitis and intussusception were seen with greater frequency in our study sample. Conclusion: Data reveals widespread asymptomatic infection among children. We may achieve herd immunity faster than other countries which might also increase vaccine effectiveness.